2022
DOI: 10.26442/00403660.2022.05.201488
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the phosphatidylserine/prothrombin complex in the diagnosis of antiphospholipid syndrome

Abstract: Aim. To determine the significance of antibodies to the phosphatidylserine/prothrombin complex (aPS/PT) in patients with systemic lupus erythematosus (SLE) antiphospholipid syndrome (APS). Materials and methods. A total of 190 patients were included in the study: 123 (64.7%) with reliable SLE and 55 (29%) with PAPS. The control group included 100 relatively healthy subjects of comparable age. All patients were tested for classical aPL as well as IgG/IgM-anti-PS/PT by enzyme immunoassay. Results. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated a link between the IgA isotypes and thrombosis (Pericleous et al, 2016;Tebo et al, 2016). Recently, Reshetnyak et al reported that IgA aCL and IgA aβ2GPI had a high specificity (95% and 93%) but a low sensitivity (54% and 44%) in detecting APS (Reshetnyak et al, 2022). The diagnostic value of IgA aPL is worthy of further study in the future.…”
Section: The Analysis Of Hotspots and Frontiersmentioning
confidence: 98%
“…Several studies have demonstrated a link between the IgA isotypes and thrombosis (Pericleous et al, 2016;Tebo et al, 2016). Recently, Reshetnyak et al reported that IgA aCL and IgA aβ2GPI had a high specificity (95% and 93%) but a low sensitivity (54% and 44%) in detecting APS (Reshetnyak et al, 2022). The diagnostic value of IgA aPL is worthy of further study in the future.…”
Section: The Analysis Of Hotspots and Frontiersmentioning
confidence: 98%